Pengaruh Pelatihan Proses Keperawatan terhadap Pendokumentasi Asuhan Keperawatan - Mayenti, Fitra; Meri, Dilgu; Efliani, Destria; Amin, Suci; Rahmadhani, Dwi Yunita (Universitas Baiturrahim, 2025)
Nursing services play an essential role in improving the quality of healthcare, with nursing care documentation serving as a key indicator of nurses’ performance. However, documentation practices in many hospitals remain suboptimal and often fall below the required standards. This Community Service Program (PkM) aimed to improve the quality of nursing care documentation through training on the nursing process based on the 3S model (Indonesian Nursing Diagnosis Standards, Nursing Outcomes Standards, and Nursing Interventions Standards) at RSIA Annisa Pekanbaru. The training was conducted over one year using seminars and hands-on practice, involving 20 inpatient nurses and nursing students. Evaluation results showed an increase in participants’ knowledge from 90% (pre-test) to 100% (post-test) after receiving the training materials. Participants also demonstrated high enthusiasm in understanding the importance of applying the 3S model to enhance documentation quality. This program successfully improved nurses’ competencies and produced outputs such as a training module, a mass media publication, and a draft manuscript for submission to a nationally accredited journal. In conclusion, training on the nursing process using the 3S approach proved effective in improving the quality of nursing care documentation and supporting the professionalism of nurses in healthcare services